A Magnetohydrodynamics Simulation of Coronal Mass Ejections in the Upper Corona at 2.5R⊙ ≤ r ≤ 19R⊙ - Keiji Hayashi; Chin-Chun Wu; Kan Liou (The Astrophysical Journal)
The methodology of a new magnetohydrodynamics simulation model of the propagation of coronal mass ejections (CMEs) in the near-Sun solar wind region at 2.5 R _⊙ ≥ r ≥ 19 R _⊙ is presented. The simulation model first determines the steady state of the transonic/Alfvénic solar wind with the characteristic-based inner boundary treatment for the middle of the corona at r  = 2.5 R _⊙ (K. Hayashi et al. 2023 ). To determine the numerical perturbation on the 2.5 R _⊙ inner boundary surface, a kinetic self-similar model with a torus-shaped magnetic-field rope and a spherically symmetric plasma structure translating and expanding at the constant speed (named TICK model) is developed. A solar-wind MHD model (C.-C. Wu et al. 2020b ) traces the temporal evolution of the injected CME through the inner boundary surface. We conducted test simulations with various choices of plasma density and temperature. The test simulation results show that the injected CME, particularly its internal magnetic structure, can be substantially altered through the interactions with the preexisting slow and dense ambient solar wind at the early phase of the propagation in the near-Sun region. The propagation speed of the discontinuity front is found to be dependent on the plasma parameters of the CME perturbation. Therefore, for better simulating the propagation of the CME, it is important for the CME models to include the nonlinear MHD interactions in the subsonic/Alfvénic regions.